Myths and facts : Bangladesh liberation war : how India, U.S., China, and the U.S.S.R. shaped the outcome - Khasru, B. Z. (New Delhi : Rupa & Co., 2010)
Chiefly with reference to diplomacy with United States and India at the time of the liberation war of 1971 of Bangladesh.
Includes bibliographical references (pages [442]-466) and index.
Keywords: Bangladesh -- History -- Revolution, 1971 -- Causes; Bangladesh -- History -- Revolution, 1971 -- Sources; Bangladesh -- Foreign relations -- United States; United States -- Foreign relations -- Bangladesh; Bangladesh -- Foreign relations -- India; India -- Foreign relations -- Bangladesh; United States -- Foreign relations -- 1969-1974.; India -- Foreign relations -- 1947-1984.